FAT AND WATER CONTENTS OF THE MUSCLE AND OVARY DURING THE MATURATION CYCLE OF PSEUDOSCIAENA ANEUS (BLOCK) AND JOHNIUS CARUTTA (BLOCH) - Rao, T Appa (Indian Journal of Fisheries, 2011)
In fishes fat accumulates mostly in muscles, liver, intestine and gonads forutilization during the reproductive activity (Milroy, 1898; Bruce, 1924; Channonand Saby, 1932; Lovern and Wood, 1937; Hickling, 1947; Bailey, 1952; Hoar, 1957;Love, 1957). Previous investigations (Milroy, 1898; Lovern and Wood, 1937;Hickling, 1947) revealed that during maturation the fats which are stored invarious organs are transferred to maturing gonads.Durairaj (1962) reviewed some previous investigations made with referenceto nutritive value and seasonal variations in fat contents of the fishes in India.'The present problem was taken up during the period of 1961-62 with a viewto studying the quantitative distribution of fat and water in flesh and ovaries indiflferent stages of maturity of Pseudosciaena aneus and Johnius carut